Bulgaria : Improving the Quality and Relevance of Education for All - World Bank (Washington, DC, 2013)
Bulgaria has recently introduced sweeping reforms of its secondary education system to promote more autonomy and accountability of schools for better learning outcomes. Positive results are already showing but more remains to be done to reap the full benefits of the reforms. Per-student-financing and delegated budgets have led to a wave of school closures that had become essential in the wake of a dramatic decline in student numbers. As opposed to the previous centralized system, school-based management with a considerable degree of decision-making power of the school principal has set the stage for schools to better adjust to local needs and opportunities for a better education. External student assessments are now routinely conducted, which have substantially improved the evidence base for education policy-making. However, concerns remain as to the accountability of schools to the local community. While principals are accountable to the municipal authorities for the use of financial resources, parents have little formal ways of holding principals accountable for learning outcomes. The reform was launched in the face of dramatic challenges in terms of unsatisfactory learning outcomes, early school leaving and considerable inequities in the education system. Moreover, Bulgaria s vocational education and training system remains un-reformed, and there are concerns with regard to the quality and relevance, with few formal communication channels to the labor market. The higher education system, meanwhile, is characterized by low participation relative to other new EU Member States, and the system of occupationally-oriented colleges, an important part of higher education across the EU, remains underdeveloped relative to academically-oriented universities. The economic crisis and associated fiscal pressures should not lead to cuts in the education budget. Promoting accountability for learning outcomes and results is the key policy direction for both secondary and tertiary education. Teachers are the key determinant of the quality of education.